Animal model of febrile seizures and epileptogenesis - Heba Mohamed Sayed Ibrahim; Haitham Sharaf Eldin Mohammed; Heba Salah Eldin; Maha Anwar Ali (Cairo : Heba Mohamed Sayed Ibrahim, 2019)
Febrile seizures (FS) are convulsions accompanied with elevation in body temperature. It{u2019}s highly prevalent in children between 6 months to 5 years old and may have detrimental effects in adulthood. In the present study, an experimental animal model of FS was designed by exposing young animals to hyperthermia. Oxidative stress parameters (malondialdehyde, nitric oxide, reduced glutathione) and acetylcholinesterase activity were analyzed in the hippocampus and cortex of immature hyperthermic and adult animals exposed to hyperthermia while immature and control animals.The electroencephalogram (EEG) was also recorded in adult hyperthermia-exposed rats. Moreover, behavioral assessment of seizure threshold and its severity was obtained by injection of a sub- convulsive dose of nicotine to adult animals. Alterations in the oxidant / antioxidant system and AchE activity occurred in the hippocampus and cortex of FS animals relative to control ones. Significant changes in all EEG frequency bands were obtained by spectral analysis of EEG of adult hyperthermia-exposed animals. Seizure susceptibility observation and scaling revealed a decrease in seizure threshold and increase in seizure severity. The present study emphasizes the correlation between prolonged FS encountered at immature age and long lasting brain abnormalities at adulthood which may be related to the underlying mechanism of epileptogenesis and its related co{u2013}morbid
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Biophysics
Issued also as CD
Keywords: Febrile seizures (FS); Hyperthermia; Oxidative stress